Diarylformamides as a Safe Reservoir and Room Temperature Source of Ultra-Pure CO in the Context of a ‘Green’ rWGS Reaction - Hurtado, Royel; Lou, Lisha; Klerner, Lukas; Dindarloo Inaloo, Iman; Heinemann, Frank Wilhelm; Harder, Sjoerd; Schmid, Günter; Dorta, Romano (Chemsuschem, 2024)
Diphenylformamide 1 and bisformamide 9 are shown to be safe reservoirs and sources of CO. Their perfectly selective decarbonylations are achieved in solution at room temperature with potassium and cesium diarylamide catalysts. 1 is obtained in excellent yields directly from triethylammonium formate, which may be the product of CO2 scrubbing with NEt3 and catalytic hydrogenation. 1 thus represents a key intermediate in a low-temperature rWGS reaction sequence. Moreover, solvent-free decarbonylations of 1 may be run either in the melt at 70 °C or with 9 even in the solid state at 88 °C with improved atom economy. These simple and practical transition-metal-free decarbonylations afford ultra-pure (i. e. dry and solvent-free) CO at moderate temperatures and the diarylamines byproducts are recycled as pure compounds. In the absence of catalysts, diarylformamides 1 and 9 are long-term stable at >200 °C. DFT-calculations indicate a reaction pathway with a rate-determining deprotonation of Ph2NC(O)H and barrier-free CO elimination from Ph2NC(O)−.
CRIS-Team Scopus Importer:2024-12-13
Keywords: catalytic decarbonylation; Low-temperature rWGS; N; N-diarylformamides; N-formylation; ultra-pure CO

Trapping of soluble, KCl-stabilized Cu(i) hydrides with CO2 gives crystalline formates - Grasruck, Alexander; Parla, Giorgio; Lou, Lisha; Langer, Jens; Neiß, Christian; Herrera, Alberto; Frieß, Sibylle; Görling, Andreas; Schmid, Günter; Dorta, Romano (Chemical Communications, 2023)
Cu(i)-Hydrido complexes supported by dibenzo[b,f]azepinyl P-alkene hybrid ligands and stabilized by electrostatic interactions in a Cu-H⋯KCl⋯BR3 arrangement can be trapped with CO2 at low temperature to afford Cu(i)-formates. The complexes are isolable with and without a pendant BEt3 group and show strong Cu-O and weak B-O interactions.
CRIS-Team Scopus Importer:2023-12-15